What about the others? Conditional cooperation, climate change perception and ecological actions - Leonardo Becchetti; Gianluigi Conzo; Francesco Salustri (Global Labor Organization (GLO), 2023)
Climate challenge can be modelled as a multiplayer prisoner's dilemma where any ecological action - i.e., purchasing an electric car or adopting sustainable life styles - is a costly action in terms of economic resources, time, and effort for individuals. According to the well-known embedded social dilemma, even though the social benefit is maximised when everyone takes ecological actions, the Nash equilibrium of the game if all players have standard self-interested preferences is not acting. In this paper we analyse how this ecological prisoner's dilemma is affected by people's perception. Using the European Social Survey, we look at how urgent the climate threat is perceived by respondents and what they think about other countries' willingness to take ecological actions. Theoretical predictions suggest that the former increases, while the latter does not affect willingness to take ecological actions. Our empirical findings on a large sample of European citizens however show that both factors positively affect willingness to take actions. We interpret the positive effect of other country action on the individual responsibility to take actions in terms of conditional cooperation and show that the effect is weaker in countries and regions with higher social capital.
Keywords: H41; Q54; Q58; 330; climate change; perception; ecological actions; social dilemma; conditional cooperation